Paciente adulta mayor con hipertensión arterial + diabetes mellitus tipo 2 - Barragán Fuentes, Lourdes Guadalupe (2018)
La hypertension arteria y la diabetes mellitus typo 2 are diseases that affect everyone and every population so it is a problem worldwide according to the Health Organization if this disease is not treated in time could lead to death. This disease has been affecting the population for many years but nowadays it is becoming a problem due to the lack of ignorance of many people also due to their sedentary lifestyle and their nutritional form. We have that diabetes is a pathology that seriously affects Ecuador, being the third cause of death in the country, an indicator that should promote the population to bring a better quality food and avoid the suffering of this disease. The word hypertension refers to a picture of high blood pressure. It is called "the silent killer" because it usually does not cause symptoms for many years (until it injures a vital organ)